Biblical Versus Hadith - Questioning Interpretation Authority in The Quran: A Reformist Translation - Yudha, Helmi (IAIN Pekalongan, 2018)
This paper explains Edip Yüksel's view of the Qur'an, the Bible and the Hadith. He set(s) up a hierarchy of authority of the holy scriptures as a land point. The Qur'an stands at the highest level of the hierarchy because it is the most authentic word of God; there is no contradiction within; it is revealed for all humanity; and is the Final Testament. The second rank is the Bible which is still be considered as God's authority over mankind, however with some contradictory messages. There is the Hadith in the last place, a level of manmade works, because it does not have Gods authority. Moreover, it is very contradictory. In an attempt to interpret the Quran, he propose(s) the realization of justice, unity and peace over mankind. For the sake of achieving those goals, the Christian scriptures are cross-referenced with the Qur'an either using direct, indirect, and referral method. The selected topics can be grouped into four kinds; theology, law, social issues, and stories. The functions of Biblical use in tafsir were to complement, to compare, and even to criticize the Bible itself. 'Critical,' is the right word to describe Edip's attitude toward the Bible.